Analysis of Legal Protection Against Consumers of Refill Drinking Water That Has Not Met Product Quality Standards - Soraya, Thalia Firda (UM Purwokerto Press, 2023)
Consumer protection is something that cannot be separated from healthy business activities. The definition of consumer protection according to Law Number 8 Year 1999 on Consumer Protection is all efforts that ensure legal certainty to provide protection to consumers. This research focuses on consumer protection against the consumption of refill drinking water with the aim of knowing the legal protection of consumers and knowing the standards and requirements for making refill drinking water. Often the standardization of the manufacture of a product is ignored because consumers are less concerned about their rights to quality assurance than a product, this is one of the factors that encourage producers to act as they wish for the goods they will market. Refillable drinking water products offered by business actors must meet the standardization of water quality standards set by the government. This research was conducted using the normative juridical method through legal and conceptual approaches. In writing this research, the author uses primary legal materials that are binding and secondary legal materials as references. The result of this research is legal certainty on consumer protection and standardization of refill drinking water production in accordance with Permenkes Number 492/Menkes/Per/IV/2010.